Papua New Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This paper examines and tests the existence of political budget cycles in Papua New Guinea during the period 1988-2004. Several factors point to the existence of political budget cycles in Papua New Guinea. The paper provides an overview of the political business cycle literature, and Papua New Guinea's political structure and processes. It also describes the data set and the empirical methods used to test for the presence of election-influenced spending, and presents the results of a time-series analysis.